Performance Characteristics of Polymer Electrolyte Membrane CO2 Electrolyzer: Effect of CO2 Dilution, Flow Rate and Pressure. Issue 6 (1st June 2022) - Karimi, Parisa; Alihosseinzadeh, Amir; Ponnurangam, Sathish; Karan, Kunal
Abstract : CO2 electrolyzer designed to operate on dilute CO2 feed and low stoichiometric ratio would alleviate the separation costs for CO2 purification and electrolyzer exit gas processing, respectively. The effect of CO2 concentration, CO2 flow rate, and CO2 pressure on current density and faradaic efficiency of a solid polymer electrolyte membrane CO2 electrolyzer was quantified. An approach for estimating voltage breakdown into activation overpotential for CO2 reduction reaction as well as oxygen evolution reaction, ohmic losses, and concentration overpotential is introduced. No enhancement in current density (∼160 mA cm −2 ) was observed above stoichiometry ratio of 4 whereas reducing the stoichiometric ratio to 2.7 still yielded a current density of ∼100 mA cm −2 . Dilution of CO2 in the feed from 100 mol% to 30 mol%, at ∼90kPa of cell pressure, resulted in a monotonically decreasing current density. A square root dependency on CO2 partial pressure was observed under these conditions. Operation with pure CO2 at different total pressure yielded only a minor increase in current density indicating some form of saturation-limited behavior. Long-term potentiostatic operation over 85 h revealed continuous drop in current density and a corresponding increase in electrode resistance, observed in electrochemical impedance response.